-3(6x-8)+7=-18+31

Simple and best practice solution for -3(6x-8)+7=-18+31 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6x-8)+7=-18+31 equation:


-3(6x-8)+7=-18+31

We simplify the equation to the form, which is simple to understand
-3(6x-8)+7=-18+31

Reorder the terms in parentheses
+(-18x+24)+7=-18+31

Remove unnecessary parentheses
-18x+24+7=-18+31

We move all terms containing x to the left and all other terms to the right.
-18x=-18+31-24-7

We simplify left and right side of the equation.
-18x=-18

We divide both sides of the equation by -18 to get x.
x=1

See similar equations:

| 2(x+7)+6=2x+2 | | 7x=5(2x-5) | | 12(r-5)=60 | | -4-4p=24 | | 3x+1-1=3x+2 | | 20x(4-2)= | | 4(7v-8)=136 | | 8X+12Y=(X+Y) | | 2(y-5)=7y+8 | | 3y-2x=m | | N^2-81n=0 | | -9p-4=50 | | -8(n-1)=5-8n | | -9p-4=40 | | =9E-07(551.368) | | 49=413c-7 | | 10(3x-5)=100x | | -5(4y-2)-y=-4(y-2) | | 6n+3n+3120=5400 | | -6+-1y=10 | | -7p-4=2p+40 | | 17=102 | | 6+-1y=10 | | 2(3s+2)=76 | | -4.9m^2+34.3m+0=58.8 | | 10(2x-11)=90x | | 2x+Y+4z=19 | | 12=15-9(3) | | 4x+2x-x= | | 13+(29+7)=13+(7+29) | | -5(x+3)=-14-4x | | R=4x+12 |

Equations solver categories